Food security of farmer households in Central Lombok Regency. - Utama, Lalu Juntra; Abdi, Lalu Khairul; Yunita, Lina; Saudia, Baiq Eka Putri; Kristiandi, Kiki; Nur, Astuti (Nutrición Clínica y Dietética Hospitalaria, 2024)
Background: Food security is a key issue in fulfilling community welfare because it will determine a country's economic, social, and political stability. Food security is a condition where food is met down to the individual level, reflected in the availability of sufficient quantity and quality and safe, diverse, and affordable food. This research analyzed the status and situation of food security of farming households and examined the determinants of food security of farming households in Central Lombok Regency. Methods: The analysis used an approach to measure regional food security based on quantitative food availability, access, and utilization indicators. Descriptive statistical analysis techniques and Tobit regression analysis to identify factors that influence household food security. The design of this research was a cross-sectional study in Central Lombok Regency, West Nusa Tenggara Province. The location selection was carried out purposively, considering that Central Lombok Regency has a high prevalence of nutritional problems. This research involved two groups of subjects: toddlers and mothers. Results: The intake of micronutrients for toddlers, including Vitamin C, iron, iodine, and calcium in Central Lombok Regency, is generally still insufficient; only vitamin A intake is categorized as sufficient on average. Intake of macronutrients, namely energy, protein, and carbohydrates, is generally above adequate; only fat intake is in the severe deficiency category. The majority of toddlers in Central Lombok Regency have good weight, height, and nutritional status. Demographic conditions, including education and the number of family members in Central Lombok Regency, are related to the Food Insecurities Scale. In Central Lombok Regency, no significant relationship was found between HDDS and overcoming food insecurity. Conclusions: Even though the intake of micronutrients in toddlers is low, the majority have good nutritional status. Food security is related to demographic conditions, and income plays an important role in overcoming food insecurity.